Plasma lipid profile of experimentally induced hyperlipidemic New Zealand white rabbits is not affected by resveratrol - De Castro, Marines [UNESP]; Veiga, Angela P. M.; Pacheco, Maria R. [UNESP] (My University, 2009)
Hyperlipidemia is well recognized as an important risk factor in the development of atherosclerosis. Low-density lipoproteins (LDL) are components of cholesterol that are highly associated to an increased risk of cardiovascular diseases. Hypercholesterolemia induces proteolytic and oxidative changes in vasculature, leading to a local inflammatory response. Since dietary antioxidants have attracted considerable attention as preventive and therapeutic agents, the polyphenolic compound resveratrol seems to play an important role in prevention of human atherosclerosis. Researches show that resveratrol inhibits LDL oxidation and platelet aggregation, as well as vascular prolifer ation of smooth muscle cells. However, recent findings in animal models reveal conflicting results regarding its effects on plasma lipid levels. The aim of the present study was to evaluate the effect of resveratrol on plasma biochemistry profile in New Zealand white rabbits submitted to a hypercholesterolemic diet. Twenty healthy, male, adult New Zealand white rabbits were fed with ordinary diet for one week before being divided into four treatment groups, containing five animals each. Group CT received maintenance diet; group R received maintenance diet and resveratrol (3mg/kg/day) given orally; group CL received maintenance diet enriched with 1.5% cholesterol; and group CR received maintenance diet enriched with 1.5% cholesterol and resveratrol (3mg/kg/day) given orally. During the experiment, from each animal, samples of 3mL venous blood were collected in heparin twice monthly for measurements of total cholesterol, triglycerides, and low- and high-density lipoproteins. The data analysis revealed that resveratrol did not have a hypolipidemic effect in experimentally induced hypercholesterolemic New Zealand white rabbits.
Keywords: Atherosclerosis; Hyperlipidemia; Resveratrol; cholesterol; heparin; high density lipoprotein; low density lipoprotein; resveratrol; triacylglycerol; animal experiment; animal model; blood sampling; cholesterol blood level; controlled study; drug effect; hyperlipidemia; lipid blood level; male; New Zealand; nonhuman; rabbit